Genetic variability of HIF1A and response to treatment with cisplatin in combination with pemetrexed or gemcitabine in patients with malignant mesothelioma - Šetina, Matic (Radiology and oncology (Ljubljana), 2025)
Background. Treatment of malignant mesothelioma (MM) still relies on chemotherapy with cisplatin in combination with pemetrexed or other drugs. Studies indicate that hypoxic conditions within tumour tissue may reduce responsiveness to cisplatin-based chemotherapy. Hypoxia-inducible factors (HIF) play an important role in regulation of cellular adaptation to hypoxia. The aim of our study was to investigate single nucleotide polymorphisms (SNPs) in the HIF1A gene coding for the regulatory alpha subunit (HIF-1A) and their role in the response to chemotherapy in patients with MM. Patients and methods. Our retrospective genetic association study included 234 patients with MM, who were treated with a combination of cisplatin/pemetrexed or cisplatin/gemcitabine at the Institute of Oncology Ljubljana between January 2001 and September 2018. Selected HIF1A SNPs (rs1154965, rs11549467, and rs2057482) were genotyped using the competitive allele-specific polymerase chain reaction (KASP). Additionally, we used a TaqMan assay for independent confirmation of rs11549465 genotyping results. The impact of the SNPs on response to chemotherapy was analysed using logistic regression. For survival analysis, we used the Kaplan-Meier method and Cox regression. Results. In heterozygotes with the HIF1A rs11549465 CT genotype, response to chemotherapy was significantly worse compared to homozygotes with the CC genotype, but only after adjustment for weight loss and CRP (ROadj = 0.37; 95% CI = 0.14–0.97; Padj = 0.044). HIF1A rs11549467 and rs2057482 were not associated with response to chemotherapy (all P > 0.05). None of the investigated SNPs were associated with progression-free survival or overall survival (all P > 0.05). Conclusions. Among the investigated HIF1A SNPs, only rs11549465 has showed association with a worse response to chemotherapy after the adjustment for clinical parameters. The findings of this study have improved our understanding of the role of HIF1A polymorphisms in MM and may offer valuable insights into their impact on other cancers as well.
Keywords: chemotherapy; kemoterapija; malignant mesothelioma; maligni mezoteliom; polimorfizem; polymorphism